2013
DOI: 10.1080/17550874.2013.848950
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal ecology on serpentine soils

Abstract: Background: Serpentine ecosystems support different, often unique, plant communities; however, we know little about the soil organisms that associate with these ecosystems. Mycorrhizas, mutualistic symbioses between fungi and roots, are critical to nutrient cycling and energy exchange below ground. Aims: We address three hypotheses: H1, diversity of mycorrhizal fungi in serpentine soils mirrors above-ground plant diversity; H2, the morphology of mycorrhizas and fungi on serpentine soils differs from that on no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 65 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Even though there are several studies on bacterial influence on heavy metal uptake in soil, very few have focussed on fungi. However, studies have reported the effect of mycorrhizal fungi on heavy metal uptake; uptake by mycorrhizal fungi depends on plant growth conditions, the fungal partner, heavy metal and amount of metal present in soil (Weissenhorn et al 1995;Southworth et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though there are several studies on bacterial influence on heavy metal uptake in soil, very few have focussed on fungi. However, studies have reported the effect of mycorrhizal fungi on heavy metal uptake; uptake by mycorrhizal fungi depends on plant growth conditions, the fungal partner, heavy metal and amount of metal present in soil (Weissenhorn et al 1995;Southworth et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Because of generally low organic matter and clay content (Proctor and Woodell 1975), serpentine soils often have a low water-holding capacity. Because of the high heavy metal concentrations, the microbial diversity is often low compared with non-serpentine soils (Panaccione et al 2001;Southworth et al 2014). Infertility, metal toxicity, and often sandy, rocky and shallow soils combined with low microbial diversity contribute to unique plant communities consisting of many rare and endemic species (Harrison and Rajakaruna 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Specialization in plant host-symbiont-soil interactions may also facilitate plant adaptation to edaphic stress and subsequent specialization (see Table 2 in Van Nuland, 2016). Arbuscular mycorrhizal fungi (AMF) are common root symbionts that can increase a plant hosts' establishment and growth in edaphically-stressful environments (Palacio et al, 2012;Schechter & Branco, 2014;Southworth et al, 2014). There are plant and microbial symbionts that enhance plant adaptation to edaphic stress (Thrall et al, 2007), showing that co-adapted interactions may play a role in edaphic specialization.…”
Section: Do Interactions With Herbivores or Microbes Drive The Evolutmentioning
confidence: 99%
“…Although both populations were able to perform similarly in serpentine soils in the short term (21 days), there was a significant difference in both above-and below-ground biomass in the serpentine population growing in serpentine soils under longterm (4 months) exposure, compared with the non-serpentine population. The lower biomass seen in the non-serpentine population when grown in serpentine soils may not be due only to Ni and other metal toxicity, but also to the deficiency of essential nutrients such as N, P, K, and Ca and moisture stress often characterising serpentine soil (Rajakaruna and Baker 2004;Alexander et al 2007) or changes in the beneficial microbiota in the two soils (Southworth et al 2014). Decreases in both above-and below-ground biomass when exposed to serpentine soils can have a significant influence on competitive ability (Moore and Elmendorf 2011) as well as reproductive fitness (Ghasemi et al 2014).…”
Section: Discussionmentioning
confidence: 99%